Autochthonous Angiostrongylus cantonensis Lungworms in Urban Rats, Valencia, Spain, 2021 - Galán-Puchades, María Teresa; Gómez-Samblás, Mercedes; Osuna, Antonio; Sáez-Durán, Sandra; Bueno-Marí, Rubén; Fuentes, Màrius V.
To determine the role of rats as potential reservoirs of zoonotic parasites, we examined rats trapped in urban sewers of Valencia, Spain, in 2021. Morphologic and molecular identification and sequencing identified autochthonous Angiostrongylus cantonensis nematodes, the most common cause of human eosinophilic meningitis, in pulmonary arteries of Rattus norvegicus and R. rattus rats.